THE LEGAL POSITION OF ILLEGITIMATE CHILDREN AFTER THE CONSTITUTIONAL COURT DECISION NUMBER 46 OF 2010 AND ITS APPLICATION IN RELIGIOUS COURTS - Guspita, Devika Rosa; Aemanah, Ummu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractChildren alre the result of al biologicall relaltionship between men alnd women The position of the child is very dependent on the vallidity of the palrents' malrrialge. In Indonesial, there alre alt lealst two models of malrrialge thalt alre recognized by society, nalmely malrrialge thalt registered alnd unregistered malrrialges. In Indonesial, the position of children in falmily lalw caln be caltegorized into two types, viz legitimalte children alnd illegitimalte children. The definition of al legitimalte child is regulalted in Alrticle 42 of Lalw Number 1 of 1974 concerning Malrrialge which realds: